2020
DOI: 10.3390/agronomy10030328
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Modeled Water Use Efficiency of Highly Productive Perennial Grasses Useful for Bioenergy

Abstract: Whole plant productivity is obviously the ultimate product of leaf photosynthesis and this has led to numerous efforts to relate the two. However, often with perennial grasses, plant productivity is more sink-limited than source-limited, causing the linkage between the photosynthetic rate and productivity to be weak or nonexistent. This has led to a different approach, characterizing plant productivity in terms of the efficiency of intercepted light use in producing biomass, also called radiation use efficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
1
1
0
Order By: Relevance
“…Previous studies on tall fescue have observed similar trends with festucoid species observed to have an optimum growth temperature between 20-27 • C [85,87,104,105]. The significant declines in biomass for tall fescue, despite little change in photosynthetic capacity, suggests that whole-plant productivity may be more sink-limited than source-limited [106], with productivity regulated by tiller production & leaf canopy orientation [107]. The significant decline in productivity for both species under warming may also be linked to the significant reduction we observed in C:N ratio, which suggests a decline in long term nitrogen use efficiency [108].…”
Section: Discussionsupporting
confidence: 60%
“…Previous studies on tall fescue have observed similar trends with festucoid species observed to have an optimum growth temperature between 20-27 • C [85,87,104,105]. The significant declines in biomass for tall fescue, despite little change in photosynthetic capacity, suggests that whole-plant productivity may be more sink-limited than source-limited [106], with productivity regulated by tiller production & leaf canopy orientation [107]. The significant decline in productivity for both species under warming may also be linked to the significant reduction we observed in C:N ratio, which suggests a decline in long term nitrogen use efficiency [108].…”
Section: Discussionsupporting
confidence: 60%
“…Therefore, plant genotypes with high drought tolerance or WUE can contribute to yield increases and enhance rangeland restoration success. Moreover, competition for water with other users e.g., weeds, makes maximizing water use efficiency vitally important (Kiniry and Kim, 2020). This is because, arid and semiarid rangelands in Africa are infested with aggressive weeds e.g., Ipomoea kituensis that often engulfs emerging grass seedlings leading to poor establishment.…”
Section: Introductionmentioning
confidence: 99%